"I don't like talking about it because that's not who I am": Challenges children face during epilepsy-related family communication. (September 2016) - O'Toole, S; Lambert, V; Gallagher, P; Shahwan, A; Austin, JK
Objectives: Childhood epilepsy not only significantly impacts a child's social relationships and psychosocial wellbeing, but it can also cause disruptions in family relations. Children living with epilepsy often rely on parental figures for guidance in relation to their condition. A paucity of research has examined the challenges for children when communicating about epilepsy with parental figures. This qualitative study explored the challenges faced by children when talking about epilepsy with their parent(s). Methods: Semi-structured interviews were conducted with 29 children (aged 6–16 years) living with epilepsy. Participants were recruited from a neurology department of a major pediatric hospital and from a national epilepsy association. Interviews were transcribed verbatim and thematically analyzed. Results: Findings revealed four themes: communication impeding normalcy, parental overprotection, parental reactions to epilepsy-related communication, and restriction of activities as a consequence of epilepsy-related communication. Discussion: The study highlights the need for a greater understanding of parent–child dialogue surrounding epilepsy and where challenges lie for children in conversing about their condition. Parents and health care professionals play a pivotal role in facilitating an environment where children feel comfortable talking about epilepsy. This information will be instrumental in the development of a communication-based intervention for families living with epilepsy.